Respuesta :

Answer:

x = 9 , y =3

Step-by-step explanation:

-3x + y = 0 ---- 1

2x -2y = -12 -----2

By elimination method:

let's first eliminate x

we can do that by making x equal in both equations

multiply equation 1 by 2 ( because 2 is the coefficient of x in equation 2 and remember we want to equate both equations)

multiply equation 2 by -3 ( because -3 is the coefficient of x in equation 2 and remember we want to equate them both)

-3x + y = 0 ×2

2x -2y = -12 ×-3

-6x + 2y = 0 ----3

-6x + 6y = 36 -----4

subtract equation 4 from 3

that will give

0-4y = -36

which is

-4y = -36

divide both sides by coefficient of y which is-4

(-4y) ÷ (-4) = (-36)÷(-4)

answer : y= 9

substitute 9 for y in equation 1

-3x + y = 0

-3x + 9 = 0

subtract 9 from both sides

-3x +9-9= 0-9

-3x = -9

divide both sides by coefficient of x which is-3

(-3x)÷(-3) = (-9÷-3)

x = 3